An Analysis of the Possible Financial Savings of a Carbon Capture Process through Carbon Dioxide Absorption and Geological Dumping - Ssebadduka, Ronald; Sasaki, Kyuro; Sugai, Yuichi (International Journal of Energy Economics and Policy, 2020)
Herein, we discuss possible ways to reduce the cost of carbon dioxide (CO2) sequestration with a special focus on the process and the solvent used. Modifications to the process to eliminate the stripper section and focus on just the CO2 adsorbing and geological dumping (CAGD) can lead to significant reductions in the sequestration cost per tonne of CO2 compared with ordinary CO2 capture and geological storage (CCS) processes. In the case of CAGD, savings of steam used in the ordinary CO2 capture process can go up to US12.7per ton of CO2 captured and additional savings on the waste disposal cost of US175/tonne of waste can be made. More savings on the energy costs for compression and cooling of the captured CO2 gas can be realized if the absorbent and flue gas/CO2 slurry is directly dumped in a geological formation. A change of the capture solvent can also make this process better economically by using the proposed substitute. Many commercially available alternatives to monoethanolamine (MEA) have been presented in this research by mainly focusing on how their loading capacity and cost compare. Aqueous Sodium carbonate (Na2CO3) has been proposed as the best material for use in the CAGD CO2 absorbing process based on the economic advantages it presents. Keywords: Cost of Carbon Dioxide, Geological Dumping, Financial Saving JEL Classifications: Q, Q5, Q54 DOI: https://doi.org/10.32479/ijeep.8800